Successful treatment of infliximab-induced psoriasiform skin lesions despite biologic therapy intensification in a paediatric patient with Crohn’s disease and primary sclerosing cholangitis - Wasilewska, Agata; Chmielowska-Trybek, Małgorzata; Sładek, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Therapy with infliximab (IFX), a tumour necrosis factor-α (TNF-α) inhibitor, has been demonstrated to be highly effective in several immune-mediated inflammatory diseases including Crohn’s disease (CD) and psoriasis, both in adult and paediatric patients. With the increasingly widespread use and longer follow-up of IFX, one unexpected adverse effect that has been reported is the occurrence of psoriasis-like lesions, mainly during the maintenance therapy. The present report was aimed at describing a new case of IFX-induced psoriasis-like lesions in a 17-year-old boy with CD and primary sclerosing cholangitis (PSC), which was successfully treated with topical agents, despite IFX therapy intensification due to loss of the clinical response.